IMPLEMENTATION OF AN INDIVIDUAL APPROACH IN SPORT - Kostyuchenko, V.F.; Zverev, V.D.; Lutkovsky, V.E.; Sukhoreva, S.M. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to scientifically substantiate the methodological approach to the implementation of the principle of individualization in sports training. Methods and structure of the study. The scientific work used: analysis and generalization of scientific and methodological literature, practical experience, pedagogical testing, ascertaining and shaping experiments. Quantitative indicators were processed using mathematical statistics with their subsequent logical interpretation. The study was conducted in the natural conditions of the training process on a group of middle-distance runners. Results and conclusions. Athletes with different indicators of qualities that affect sports fitness can be at the same level in the sports hierarchy. This is due to the presence of individual compensatory capabilities. The same sports result has a different individual "value" and, therefore, it is obtained by each individual athlete at a different "price". In the course of the study, it was determined that the implementation of the principle of individualization in sports training consists in organizing a pedagogical process based on an individual assessment of the relationship between a sports result and the components of an athlete’s preparedness that determine it, in building a quantitatively expressed model of an athlete’s preparedness for a certain time and the implementation of corrective actions on the level of preparedness of the athlete.